Polityka pieniężna EBC a spójność gospodarcza i społeczna - Borowiec, Jan (The ECB's Monetarny Policy Versus Economic and Social Cohesion of the European Union, 2008)
The article aims to define the role of the ECB's monetary policy in cohesion reinforcement within the European Union. Greece, Ireland, Portugal, and Spain set an example. The monetary policy has had a positive impact on economic and social cohesion, mainly through the price stability and the financial conditions, which it has established. Due to price stability maintenance, these countries have managed to avoid the negative impact of the inflation on economic growth. The real interest rates were followed by the growth in investment. Since the ECB's monetary policy was not adjusted to the cyclical variability of the national economies, it has not supported the sustainable economic growth through the output stabilization. Thus, more often it had a more pro-cyclical rather than counter-cyclical manner. This statement refers to expansive policy itself, but in this case, the inflation which accompanied the pro-cyclical policy was not relevant enough to be able to hamper the real convergence processes in the countries studied. (original abstract)
Prace Naukowe Uniwersytetu Ekonomicznego we Wrocławiu = Research Papers of Wrocław University of Economics; 2008; Nr 19, s. 55-68